Modelling of belt-driven high-speed laser beam manipulator / Muhammad Azmi Ayub, Pavel Hynek and Mike Jackson - Ayub, Muhammad Azmi; Hynek, Pavel; Jackson, Mike (UiTM Press, 2010)
This paper deals with a linear belt-driven servomechanism in the development of high-speed laser beam manipulator. The objectives of this paper are to accurately model the belt-driven mechanism and determine its resonance frequencies, phase margin and bandwidth. The use of timing belt to convert rotary to linear motion provides a cost-effective solution that can achieve high agility, high efficiency and long travel distance. However, the use of belt-drive causes uncertain dynamic behaviour and resonance problems because of its elasticity that leads to vibrations, compliance, and higher friction. Consequently, complex control strategies are required for effective control of the laser-beam trajectory planning. To reduce these problems, a complete information about system dynamics of the belt-driven mechanism is required and a comprehensive state-space model of belt-driven servomechanism is developed and presented in this paper. Frequencies response approach is used to determine the resonance for accurate control strategy of the manipulator trajectory planning.